PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IPS SMAN 2 SIAK - Sopian, Sopian; Gimin, Gimin; Syabrus, Hardisyem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of cooperative learning model number head together (nht) on the economic learning outcomes of XI IPS class students of SMAN 2 Siak Hulu. This research was conducted at SMAN 2 Siak Hulu 2018/2019 academic year. This research is in the form of a quasi-exspremental experiment. The population of this study amounted to 187 students from 6 classes while the study sample amounted to 61 students. For the experimental class there were 31 students and for the control class there were 31 students with sampling using the multystage method. The research instruments used were learning devices (syllabus, RPP, LKPD) and data collection tools (pretest and poststest, observation and documentation sheets). Analysis of the two groups used homogeneity test, t-test and achievement data test (N-GAIN). From the results of the analysis it was found that at the first meeting the average teacher activity was 66.67%, at the second meeting 87.50% and at the third meeting 95.83%. While the average student activity at the first meeting was 58.33%, at the second meeting 66.67% and at the third meeting 83.33%. Furthermore, the results of the homogeneity test found that the Levene Statistic value for both classes was 0.004 and it can be said that the posstest data of the two classes was homogeneous. Then from the results of the t test found at 4.176 and the significance level of P 0.000. These results indicate the poststest level of the two classes is different. To see the effect of cooperative learning model number head together (nht) on the economic learning outcomes of students using the N-GAIN test of the N-GAIN value obtained by 0.40 lies in the score 0.7> gain> 0.3. While the magnitude of the increase in the experimental class learning outcomes was 16.81 (30.70%) and the control class increased by 7.77 (13.77%). It can be concluded that the cooperative learning model number head together (nht) has an effect on the learning outcomes of the experimental class students in the moderate and feasible category to be considered as one of the learning models used in the learning process.Key Words: cooperative learning model number head together (nht), learning Achievement